Hydroxymethylfurfural in honey: a public health problem - Bruno Soares Toledo; Lévison da Costa Cipriano; Thais Regina de Castro Pereira; Sérgio Borges Mano; Adriano Gomes da Cruz; Erick Almeida Esmerino; Eliane Teixeira Mársico (The Journal of Engineering and Exact Sciences)
Honey is a sweet and natural product of high nutritional value, produced by honey bees (Apis mellifera) composed mainly of water and carbohydrates, nitrogen compounds, enzymes, organic acids, amino acids, phenolic compounds, flavonoids, vitamins, minerals and other phytochemical substances. For cultural reasons, it is widely used for therapeutic purposes for various. However, despite this factor, it is the most fraudulent food in Brazil. On the other hand, it is also marketed in many places without any control, with the appeal of "natural product". Due to its composition can form a compound called 5-hydromethylfurfural or HMF (a furanic ring with functional groups of aldehyde and alcohol), classified as an organic molecule produced from the degradation of sugar after the Maillard reaction that has harmful effects on consumer´s healthy. The main objective of this study was to monitor the quality of honey, a product consumed broadly and increasingly by the population as food and/or medicine. We analyzed 34 honey samples without labeling and/or any type of inspection (US - unregistered samples) obtained in commercial establishments and from unlegalized vendors in the region between the cities of Itatiaia, Resende, Penedo and Visconde de Mauá, all in the Rio de Janeiro State; and 20 samples that had label and identification (RS - registered samples). Aiming to compare the two groups, relevant analyses were performed: pH, Lugol test, Lund test, color and especially 5-HMF. It was concluded that low-cost physicochemical analyses can be used to ensure a fraud-free and quality product that there is no presence of HMF at high concentrations.